Sugaring the Pill Ethics and Uncertainties in the Use of Sucrose for Newborn Infants - Wilkinson, D; Savulescu, J; Slater, R (2012)
Sucrose is widely used for the management of procedural pain in newborn infants, including capillary blood sampling, venepuncture, and vascular cannulation. Multiple randomized controlled trials have demonstrated that sweet-tasting solutions reduce behavioral responses to acute painful stimuli. It has been claimed that sucrose should be a standard of care in neonatal units and that further placebo-controlled trials of sucrose are unnecessary and unethical. However, recently published data cast doubt on the analgesic properties of sucrose. We review this new evidence and analyze the philosophical and ethical questions that it raises, including the "problem of other minds." Sugar may be better understood not as an analgesic, removing or relieving pain, but as a compensating pleasure. There is a need for further research on the mechanism of sucrose's effect on pain behavior and on the long-term effects of sucrose treatment. Such trials will require comparison with placebo or with other interventions. Given uncertainty about the benefit of sucrose, it may be wise to use alternative analgesics or non-pharmacological interventions where these are available and appropriate. Sucrose may not be the answer to procedural pain in newborns.